Testing the Weiss-Harter-Model: Physical Activity, Self-Esteem, Enjoyment, and Social Support in Children and Adolescents - Jekauc, Darko; Mnich, Carina; Niessner, Claudia; Wunsch, Kathrin; Nigg, Claudio R.; Krell-Roesch, Janina; Woll, Alexander (Frontiers in Psychology, 2019)
Background: Several theories have been established to explain physical activity (PA) participation. However, many of these theories might not be applicable to adolescent PA behavior as they require a high level of cognitive reflection. Weiss suggests a model for youth which is based on the theoretical concept of Harter, focusing on self-esteem within social, emotional, and developmental aspects to explain behavior. The aim of this study was to test the original and a social support focused alternative version of the Weiss-Harter-model, and to cross-validate the findings in two separate studies. Methods: Data from two cross-sectional studies was retrieved and the models tested using structural equation modelling. Participants aged 11-17 years were recruited from a school (Study 1: N=182) and from the German MoMo study (Study 2: N=2,274). They filled in questionnaires about perceived competence, social support, self-esteem, PA enjoyment, and minutes of moderate-vigorous PA (MVPA). Results: None of the studies showed a good model fit for the original model (Study 1: CFI=.870, RMSEA .118 [90% CI .081-.158], χ2 = 38.7, p<.01; Study 2: CFI=.871, RMSEA .148 [90% CI .140-.155], χ2=1112.6, p<.01), explaining only 12% and 17% of MVPA variance, respectively. The alternative model which added the direct paths of social support to MVPA and PA enjoyment had a very good model fit for both Study 1 (CFI=1.000, RMSEA .000 [90% CI .000-.031], χ2=4.8, p>.05) and Study 2 (CFI=.990, RMSEA .043 [90% CI .035-.051], χ2=103.7, p<.01). The addition of these paths led to changes in effect size and directions of other path coefficients, with self-esteem having a small to meaningless impact on MVPA. The revised models accounted for 38% and 42% explained variance in MVPA, respectively. Discussion: The prominent role of self-esteem in the original model could not be confirmed. Instead, the results emphasize the role of social support for PA and PA enjoyment, which is in line with current research. Interventions to increase adolescent PA levels should thus focus more on components of social support instead of self-esteem. Future studies are needed to examine the interplay between social support, PA enjoyment and perceived competence as PA determinants.